Ethiopian Herbal Medicine Practice and the Recognition with Modern Medicine - Abay, Solomon Mequanente (Pharmacognosy Reviews)
Countries in Africa, Asia, and Latin America use traditional medicine to help meet some of their primary health care needs. Use of traditional medicine for primary health care is extensive in Ethiopia –90 %. Ethiopian herbalists use different types and parts of plants with medicinal value. The traditional medical practices and remedies are recorded in oral traditional and in early medico – religious manuscripts and traditional pharmacopoias, which, according to the estimates of some historians, date back to the 15th century AD. Drugs are prepared in various dosage forms including liquid (e.g. solution, suspension), semisolid (e.g. ointment) and solid (e.g. powder). Ethiopian government firmly recognizes the traditional medicine, mainly herbal medicine. A significant number of people depend on herbal medicine even if it is not part of conventional health care system. The development of herbal medicine is greatly affected by environmental degradation, poor resource management, urbanization and lack of awareness on the contribution of herbal medicine. Responsible body- government and the public at large- should be recommended to initiate the implementation of the policy through developing rules and regulations on co-recognition or integration of herbal medicine. As medicinal plant is a resource affected by environmental degradation, it is wise to implement environmental protection policy. People awareness on herbal medicine needs to be improved by mainstreaming of course on this area especially for students of modern health science concept. In addition to this, delivering formal training and organizing of the on job herbalists is necessary.
Keywords: Ethiopia; Herbal medicine; Co-recognition; Integration